Experimental Analysis of Self Compacting Concrete by Replacing Sand with Stone Dust (International Journal of Innovative Research in Engineering & Management, 2022)
Self-compacting concrete (SCC) is defined  as concrete that can be placed normally and will flow under  its own weight while maintaining its homogeneity. Full  compaction and strength may therefore be achieved without  the assistance of mechanical vibrations. Its development  was based on the desire to improve the quality of concrete  work and automate construction. It was developed in  1988.Since then, various investigations have been carried  out and mainly large constructions companies have used the  concrete in practical structures in Japan. Here in this report  an attempt has been made to study the characteristics of self compacting concrete and the specialties in the mix design,  which had given it the self-compacting capacity.
Keywords: Concrete; vibrations; strength; flow ability